Interaction of magnetic reconnection and Kelvin‐Helmholtz modes for large magnetic shear: 1. Kelvin‐Helmholtz trigger. Issue 2 (3rd February 2014) - Ma, Xuanye; Otto, Antonius; Delamere, Peter A.
<x xml:space="preserve">Abstract</x> At the Earth's magnetopause, both magnetic reconnection and the Kelvin‐Helmholtz (KH) instability can operate simultaneously for southward interplanetary magnetic field conditions. The dynamic evolution of such a system can be expected to depend on the importance of KH wave evolution versus reconnection and therefore on the respective initial perturbations. In this study, a series of local three‐dimensional MHD and Hall MHD simulations are carried out to investigate the situation where the Kelvin‐Helmholtz instability is initially the primary process. It is demonstrated that magnetic reconnection is driven and strongly modified by nonlinear KH waves. The highest reconnection rate is close to the Petschek rate, but the total open flux is limited by the size of the nonlinear KH wave. Most of the total open magnetic flux has no flux rope structure and originates from reconnection at thin current layers which connect adjacent vortices. In contrast, complex flux ropes generated by patchy reconnection within the KH vortices dominate the vicinity of the equatorial plane; however, the associated open flux with flux ropes is a minor contribution to the total open flux. Although the presence of Hall physics leads to a fast early increase of the reconnection rate, the maximum reconnection rate and the total amount of open magnetic flux at saturation are the same as in the MHD case.